Analysis of initial ability factors causing students' low mathematical literacy abilities - Sepina Lestiani; Ratih Handayani (Universitas Muhammadiyah Lampung, 2026)
Mathematical literacy is a crucial competency at the high school level, but its achievement is often hampered by unmet prior knowledge. This study aims to analyze students' low mathematical literacy by identifying indicators of unmet prior knowledge. Using a qualitative descriptive method, this study involved three eleventh-grade science students at SMAN 2 Kotabumi, selected using a purposive sampling technique based on their low literacy category. Data were collected through two instruments: a three-item mathematical literacy test and a semi-structured interview guide. The results indicate that the inability to mathematical literacy stems from a weak mastery of prerequisite material and misconceptions about basic concepts, particularly decimal numbers. Collectively, the study subjects experienced difficulties in connecting prior knowledge with new knowledge, thus hindering the development of systematic problem-solving strategies. These findings confirm that without strong prior knowledge, students cannot fully implement the mathematical literacy process. The implications of this study indicate the need to strengthen diagnostics of prerequisite material and refine basic concepts before entering more complex material.